Wheat Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2005)
This publication projects a budget that reflects expected income and costs based on wheat production in south central Kansas.
MF574_2005_10
Keywords: MF574; Economics; Crops; MF